Differences in soft tissue damage using a percutaneous versus open approach for antegrade straight humeral nailing: a quantitative and qualitative anatomical study. (18th May 2021) - Fang, Christian; Yee, Dennis KH; Wong, Tak Man; Fang, Evan; Pun, Terence; Lau, Tak Wing; Wong, Janus; Leung, Felix; Liu, Rong; Cheung, Chun Chung; Tipoe, George Lim; Leung, Frankie
Background: Percutaneous insertion of third-generation straight humeral nails is a recent alternative to the conventional open method. Rather than splitting, retracting and subsequently repairing the supraspinatus fibers to visualize the humeral head entry site, the percutaneous approach utilizes a cannulated awl to enter the intramedullary canal through the supraspinatus fibers without visualizing internal shoulder structures. Despite recent evidence demonstrating satisfactory outcomes in the percutaneous method, the potential for iatrogenic injury to the rotator cuff and other shoulder structures is not fully understood. Materials and Methods: We performed an anatomical study of 46 shoulders in 23 cadavers to compare damage caused to internal shoulder structures between the open and percutaneous techniques. Dimensions and morphologies of supraspinatus and humeral head perforations were recorded. Results: The percutaneous technique produced greater latitudinal tearing ( p = 0.002) and less longitudinal tearing ( p < 0.001) of muscle fibers, however there was no difference in supraspinatus hole area ( p = 0.748). The long head biceps tendon was within 3 mm of the bone entry hole in 13 (28%) shoulders, with one shoulder in the open group exhibiting full tendon transection. Conclusions: Percutaneous insertion of intramedullary nails using a cannulated awl appears to produce similar soft tissue and bone entry site morphology as compared to the conventional open technique. The percutaneous method was associated with slightly greater latitudinal tearing, however the effects of this remain to be clarified through clinical studies. External rotation should be avoided during instrumentation to reduce the risk of biceps tendon transection.